1978
DOI: 10.1161/01.res.43.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a splanchnic sodium input monitor regulating renal sodium excretion in man. Lack of dependence upon aldosterone.

Abstract: SUMMARY Eight normal male subjects were placed on a constant 10 mEq sodium, 60 mEq potassium diet for 5 days. At 8:00 a.m. on the 5th day, the subjects were given a standard dose of 100 mEq of sodium orally or intravenously. Subjects receiving oral sodium also received 200 ml of 5% dextrose in water intravenously, and those receiving intravenous sodium also received placebo capsules orally. Water intake and posture were controlled. The subjects then returned to a free diet for 1 month and subsequently were res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 13 publications
4
51
0
2
Order By: Relevance
“…The hypothesis of a regulatory mechanism linking the gastrointestinal tract and kidney is not new. Evidence of a gastrointestinal monitor for sodium balance was considered from the observation that an equivalent sodium load is more rapidly excreted after oral administration, compared with intravenous administration (6,34). Otherwise, it has been suggested that guanylin peptides are responsible for this regulatory mechanism linking intestinal and renal transport of water and electrolytes (19).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of a regulatory mechanism linking the gastrointestinal tract and kidney is not new. Evidence of a gastrointestinal monitor for sodium balance was considered from the observation that an equivalent sodium load is more rapidly excreted after oral administration, compared with intravenous administration (6,34). Otherwise, it has been suggested that guanylin peptides are responsible for this regulatory mechanism linking intestinal and renal transport of water and electrolytes (19).…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that other factors play a role in this process and that the role of aldosterone is minimal in the adaptation to high-sodium meals. Carey and others [2][3][4] have demonstrated that salt-depleted individuals who were given oral sodium chloride excreted much more sodium in their urine than did individuals who were given the same amount of sodium chloride intravenously. Plasma aldosterone Published online ahead of print.…”
Section: Enteric Modulation Of Renal Sodium and Potassiummentioning
confidence: 99%
“…This conclusively demonstrates that the exaggerated response to oral sodium chloride loading is independent of aldosterone. 2 Carey 2 suggested the data also indicate "the presence of a splanchnic input monitor for sodium which partially regulates renal sodium excretion and is not dependent upon a turn-off mechanism for sodium excretion." By implication, an effector substance or mechanism to signal the kidney to increase its capacity to increase sodium excretion must exist.…”
Section: Enteric Modulation Of Renal Sodium and Potassiummentioning
confidence: 99%
“…Thus, uroguanylin has biological activity consistent with a peptide hormone that influences renal function by regulating the urinary excretion of sodium chloride as a physiological mechanism that contributes to the maintenance of Na + balance in the body. A natriuretic peptide such as uroguanylin was predicted to exist in the digestive system for release into the bloodstream for the purpose of stimulating the urinary excretion of NaCl following a salty meal (26,27). Uroguanylin is a prime candidate for this intestinal natriuretic hormone because it is produced at extraordinarily high concentrations in the upper small intestine and is released following a high salt meal (28)(29)(30)(31)(32).…”
Section: Physiological Actions Of Guanylin Peptidesmentioning
confidence: 99%
“…Uroguanylin and prouroguanylin are also found in the circulation and it is likely that the gastrointestinal (GI) tract is a main source of the plasma peptides (7,33,34). Secretion of uroguanylin from GI mucosa into the plasma in response to oral NaCl may explain the prolonged increase in urinary sodium excretion that occurs following a high salt meal (26,27).…”
Section: Physiological Actions Of Guanylin Peptidesmentioning
confidence: 99%